2022
DOI: 10.3390/w15010130
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Surface Water Quality Using the Water Quality Index (IWQ), Multivariate Statistical Analysis (MSA) and Geographic Information System (GIS) in Oued Laou Mediterranean Watershed, Morocco

Abstract: Surface water is used for a variety of purposes, including agriculture, drinking water, and other services. Therefore, its quality is crucial for irrigation, human welfare, and health. Thus, the main objective is to improve surface water quality assessment and geochemical analysis to evaluate anthropogenic activities’ impact on surface water quality in the Oued Laou watershed, Northern Morocco. Thirteen surface water samples were characterized for 26 physicochemical and biological parameters. In this aspect, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 100 publications
1
20
0
Order By: Relevance
“…Along the river, the readings of BOD5, Na, Cl, Mg, SO 4 , Ca, TH, and NO 3 were higher in the dry season than they were in the wet season, while other readings levels of HCO 3 , EC, TDS, and K were higher in the wet season than they were in the dry season. The results found that the readings of WQI for sites (1-7) classified the WQ for drinking uses as poor, and classified the WQ at sites (8)(9)(10)(11) as good. During the wet and dry seasons in 2016, the Inverse Distance Weighted (IDW) technique, as a tool in the GIS, has used to create the distributing maps of WQI for the total length of the river.…”
Section: Previous Related Studiesmentioning
confidence: 99%
“…Along the river, the readings of BOD5, Na, Cl, Mg, SO 4 , Ca, TH, and NO 3 were higher in the dry season than they were in the wet season, while other readings levels of HCO 3 , EC, TDS, and K were higher in the wet season than they were in the dry season. The results found that the readings of WQI for sites (1-7) classified the WQ for drinking uses as poor, and classified the WQ at sites (8)(9)(10)(11) as good. During the wet and dry seasons in 2016, the Inverse Distance Weighted (IDW) technique, as a tool in the GIS, has used to create the distributing maps of WQI for the total length of the river.…”
Section: Previous Related Studiesmentioning
confidence: 99%
“…The Mountain Pass deposit in California, discovered in 1949, made Australia and the United States key players. The U.S. dominated production from 1965 to 1995 [45,46]. However, China began to strengthen its industrial power and enter global trade in the late 1970s.…”
Section: Literature Review and Rare Earth Data Sourcesmentioning
confidence: 99%
“…These indicators provide vital information on the potential risk of sodium and magnesium hazards posed by irrigation water to soil and crops. Below are the equations of the indicators, which were adopted from [34]:…”
Section: Determination Of the Irrigation Water Quality Characteristic...mentioning
confidence: 99%